Risk of development of orthorexia nervosa and eating behavior in university students - Vital, Aline Nataly Soares (2017)
The risk of developing orthorexia nervosa and eating behavior in university students is assessed by a qualitative/quantitative, descriptive and transversal research in an institution for higher education in the state of Pernambuco, Brazil. Two questionnaires were handed out for data collection: Orto-15 assessed risks in developing orthorexia nervosa; a questionnaire on eating frequency investigated food consumption. Forty male and female students, over 18 years old, in the first and seventh period of the Physical Education course, were evaluated. Results showed that 33 (82.5%) students revealed risk trends for the development of orthorexia nervosa, predominantly males (88%). Students of the first period presented greater risk when compared to those in the seventh one. Healthy choices predominated when eating habits were analyzed. Data analysis showed that risk behavior was prevalent for the development of orthorexia nervosa in the population under analysis.